Digital assessment and quantification of pelvic organ prolapse (DPOP-Q): a randomised cross-over diagnostic agreement trial. Issue 3 (March 2016) - Thiagamoorthy, Ganesh; Zacchè, Martino; Cardozo, Linda; Naidu, Madhu; Giarenis, Ilias; Flint, Richard; Srikrishna, Sushma; Robinson, Dudley
Abstract Introduction Pelvic Organ Prolapse Quantification (POP-Q) system, measured in centimetres using a ruler (e.g. POPstix®), is recommended to quantify prolapse severity. POPstix® are costly (US $1/ruler). Home-made devices are used instead, but these have not been shown to be reproducible. Hypothesis Digitally assessed POP-Q (DPOP-Q) is as reliable, reproducible and acceptable as POP-Q assessed using POPstix®. Methods In this randomised crossover diagnostic agreement trial, each assessor measured the index finger of their dominant hand using a ruler. At visit one, patients were randomised to either POPstix® POP-Q assessment in a modified lithotomy position or DPOP-Q in both modified a lithotomy and a standing position. After the first clinician conducted this assessment, a second blinded clinician then carried out the remaining assessment on the same patient. For each examination, duration was recorded, along with a patient-completed discomfort score. Twenty-five women were invited for visit two, at which DPOP-Q was recorded by the same clinician who undertook DPOP-Q at the first visit. This allowed evaluation of inter- and intraobserver agreement together with examination acceptability. Results One hundred and nine women were recruited [median age 55 years, parity 2, body mass index (BMI) 27.1]. Of the 25 patients invited, 23 returned for visit two. DPOP-Q had high interobserver reliability [κ = 0.94, 95 % confidence interval (CI) 0.878–0.996] and intraobserver reliability (α = 0.96) with POPstix®. DPOP-Q was significantly quicker (p  = 0.02) and less uncomfortable (p  < 0.01) than POPstix® POP-Q. Conclusion DPOP-Q is reliable, acceptable and cost effective.